2006
DOI: 10.1038/sj.bjc.6603270
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant gemcitabine and concurrent radiation for patients with resected pancreatic cancer: a phase II study

Abstract: The safety and efficacy of gemcitabine and concurrent radiation to the upper abdomen followed by weekly gemcitabine in patients with resected pancreatic cancer was determined. Patients with resected adenocarcinoma of the pancreas were treated with intravenous gemcitabine administered twice-weekly (40 mg m À2) for 5 weeks concurrent with upper abdominal radiation (50.4 Gy in 5 1 2 weeks). At the completion of the chemoradiation, patients without disease progression were given gemcitabine (1000 mg m À2 ) weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Regine et al 32 noted that the addition of gemcitabine before and after 5-FU-based chemoradiation therapy resulted in a nonsignificant improvement in survival compared with 5-FU-based chemoradiation therapy alone, although local control was not specifically reported in this study. Others [33][34][35] have reported that combining irradiation with gemcitabine 33,34 or targeted agents 35 may result in improved local and distant control in patients with resected pancreatic adenocarcinoma. Although in the current study we did not find any association between local recurrence and radiation dose (40 versus 50.4 Gy), doses of >54 Gy may be necessary to improve locoregional outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Regine et al 32 noted that the addition of gemcitabine before and after 5-FU-based chemoradiation therapy resulted in a nonsignificant improvement in survival compared with 5-FU-based chemoradiation therapy alone, although local control was not specifically reported in this study. Others [33][34][35] have reported that combining irradiation with gemcitabine 33,34 or targeted agents 35 may result in improved local and distant control in patients with resected pancreatic adenocarcinoma. Although in the current study we did not find any association between local recurrence and radiation dose (40 versus 50.4 Gy), doses of >54 Gy may be necessary to improve locoregional outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…However, the acute toxicity reported was higher than in the current study (grade 3 and 4 hematological 26 %, grade 3 and 4 gastrointestinal 13 %). 22 Van Laethem et al investigated in multicenter phase II trial feasibility and toxicity of gemcitabine-based CRT regimen after R0 resection of pancreatic head cancer. After surgery, 90 patients were randomly assigned to receive either 4 cycles of gemcitabine (control arm) or gemcitabine for 2 cycles followed by weekly gemcitabine with concurrent radiation (50.4 Gy; CRT arm).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 2 previously published meta-analyses also did not show any consistent benefit for adjuvant CRT [15, 16]. Thus, only well-designed randomized studies using modern CRT regimens (including intensified modulation radiotherapy, 5-FU as continuous infusion or gemcitabine, and even targeted agents) will be able to better define the role of radiation treatment in the adjuvant setting [22,23,24,25]. …”
Section: Discussionmentioning
confidence: 99%